EFFECT OF INTELLECTUAL CAPITAL AND INTELLECTUAL CAPITAL DISCLOSURE ON FIRM VALUE - Subaida, Ida; Nurkholis, Nurkholis; Mardiati, Endang (Jurnal Aplikasi Manajemen, 2018)
This research aims to review, analyze, and provide empirical evidence about the influence of intellectual capital, intellectual capital disclosure, and financial performance on listed companies in Indonesia Stock Exchange. The population of this research is 525 companies listed in Indonesian Stock Exchange 2011-2015. 365 companies were taken as a sample of this research using purposive sampling method. The research method used was multiple linear regression analysis. Intellectual capital was measured using VAICTM; intellectual capital disclosure was measured using intellectual capital disclosure index; corporate financial performance was measured using Return of Assets (ROA), and firm value was measured using Tobin’s Q. This study found that intellectual capital has no effect on firm value, while intellectual capital disclosure and corporate financial performance have positive influence on firm value. Future research is suggested to use cross-country companies as the sample.